THE POTENTIAL OF DENTAL CEMENT ADHESION FOR FIXING FRACTURED DENTAL STRUCTURES IN ANTERIOR TEETH - Cristian Cojocariu; Monica Tarcea; Dorin Ioan Cocoș (Romanian Dental Association for Education, 2024)
The front teeth play a crucial role in facial aesthetics and masticatory functionality. Their fractures represent a significant challenge in restorative dentistry. This article aims to explore and discuss the different types of dental cement used in restorative dentistry, focusing on how they contribute to the effective and aesthetic adhesion of restorations. Dental cement, used to fix fractured dental structures, must provide long-lasting adhesion, strength, and aesthetics. Therefore, selecting the appropriate material and the correct application is essential for the success of the treatment. The included studies demonstrate significant variation in success and failure rates depending on the type of cement used and the application technique. Composite resin-based cements showed a higher success rate than glass ionomers, due to their superior adhesion and strength properties. Dental cements based on composite resin are preferred for repairing fractured front teeth due to their exceptional performance in conditions of humidity and mechanical stress. However, the selection of cement type should be guided by the specific clinical context and individual needs of the patient.